Pipistrellus nathusii ... - Honacki, James H.; Kinman, Kenneth E.; Koeppl, James W. (Zenodo, 1982)
Pipistrellus nathusii (Keyserling and Blasius, 1839). Arch. Naturgesch., 5(1):320. TYPE LOCALITY: Germany, Berlin. DISTRIBUTION: W. Europe to Urals, Caucasus, and W. Asia Minor; S. England. ISIS NUMBER: 5301405014019034001. ... : Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Chiroptera, pp. 111-215 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 199, DOI: 10.5281/zenodo.7352990 ...